Would Happiness Be Able to Mediate CSR to Increase Corporate Performance? - Amdanata, Donal Devi; Herawati, Yesi; Dewi, Nurrahma; Annisava, Aulia Rani (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) on company performance and the role of the happiness index as a mediating variable. The happiness index has become a measure of well-being. Happiness is something abstract and qualitative but is starting to be used as a measuring tool. This research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, using a purposive sampling method involving 24 companies. Data was obtained from the company's financial statements, the World Happiness Report publication, and the Indonesian Statistics. Quantitative data analysis was carried out using the SmartPLS program. The results showed that CSR has no significant effect on company performance or the happiness index, while the happiness index has a significant effect on company performance. However, the happiness index does not mediate the relationship between CSR and corporate performance.